A spatial filtering approach for Directional Audio Coding - Kallinger, Markus; Ochsenfeld, Henning; Del Galdo, Giovanni; Kuech, Fabian; Mahne, Dirk; Schultz-Amling, Richard; Thiergart, Oliver (126th Audio Engineering Society Convention 2009, 2009)
In hands-free telephony, spatial filtering techniques are employed to enhance intelligibility of speech. More precisely, these techniques aim at reducing the reverberation of the desired speech signal and attenuating interferences. Additionally, it is well-known that the spatially separate reproduction of desired and interfering sources enhance intelligibility of speech. For the latter task, Directional Audio Coding (DirAC) has proven to be an efficient method to capture and reproduce spatial sound. In this contribution, we propose a spatial filtering processing block, which works in the parameter domain of DirAC. Simulation results show that compared to a standard beamformer the novel technique offers significantly higher interference attenuation, while introducing comparably low distortion of the desired signal. Additional subjective tests of speech intelligibility confirm the instrumentally obtained results.
CRIS-Team Scopus Importer:2025-11-10